Perpaduan Gaya Bangunan pada Gereja Santo Yoseph Rancangan F.J.L. Ghijsel di Matraman, Jakarta Timur - Kirana Chandra Bestari; Dian Sulistyowati (Penerbit BRIN (BRIN Publishing), 2026)
Abstract. A Combination of Architectural Styles at St Joseph’s Church, designed by F.J.L. Ghijsels, in Matraman, East Jakarta. Santo Yoseph Church in Matraman is one of the early twentieth-century church buildings in Jakarta designed by F.J.L. Ghijsels. This study aims to identify the architectural style applied to the building and to situate it within the development of colonial architecture during the 1920s. The research was conducted through four stages: data collection, data processing, analysis, and interpretation. The main research problem concerns how the architectural character of Santo Yoseph Church can be categorized based on an analysis of its form and building components. The study employs formal analysis, stylistic analysis, and comparative analysis to examine the building style. The results indicate that the church does not represent a single stylistic category but instead demonstrates a character of colonial eclectic architecture. The basilica plan reflects the tradition of classical ecclesiastical architecture, Indies elements appear in adaptations to the tropical climate, and early twentieth-century influences are visible in the treatment of openings and decorative details. This synthesis places the building within a transitional phase toward colonial modern architecture. The study contributes to a broader understanding of the development of colonial architectural styles in early twentieth-century Indonesia. Keywords: Colonial building style, Catholic church, Saint Joseph Church, Colonial eclectic architecture Abstrak. Gereja Santo Yoseph Matraman merupakan salah satu bangunan gereja awal abad ke-20 di Jakarta yang dirancang oleh F.J.L. Ghijsels. Penelitian ini bertujuan mengidentifikasi gaya arsitektur yang diterapkan pada bangunan tersebut serta menempatkannya dalam konteks perkembangan arsitektur kolonial pada dekade 1920-an. Penelitian ini menggunakan empat tahapan yaitu pengumpulan data, pengolahan data, analisis, dan interpretasi. Permasalahan utama penelitian ini adalah bagaimana karakter gaya bangunan Gereja Santo Yoseph dapat dikategorikan berdasarkan analisis bentuk dan komponennya. Dalam menganalisis gaya bangunan digunakan metode analisis bentuk (formal analysis), analisis gaya (stylistic analysis), dan analisis komparatif (comparative analysis) Hasil kajian menunjukkan bahwa bangunan ini tidak merepresentasikan satu langgam tunggal, melainkan memperlihatkan karakter arsitektur kolonial eklektik. Denah basilika merefleksikan tradisi arsitektur gereja klasik, unsur Indis tampak pada adaptasi terhadap iklim tropis, sementara pengaruh gaya awal abad ke-20 terlihat pada pengolahan bukaan dan detail dekoratif. Perpaduan tersebut menempatkan bangunan ini dalam fase peralihan menuju arsitektur kolonial modern. Kajian ini memberikan kontribusi dalam memahami dinamika perkembangan gaya arsitektur kolonial di Indonesia pada awal abad ke-20. Kata kunci: Gaya bangunan kolonial, Gereja katolik, Gereja Santo Yoseph Matraman, Eklektisme kolonial